Prolonged neonatal jaundice with deranged thyroid function test - Choo, Jin Earn; Chellappah Thambiah, Subashini; Samsudin, Intan Nureslyna (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Congenital central hypothyroidism (CCH) is a rare disorder that results from deficient biosynthesis of thyroid hormone due to defective thyroid gland stimulation by thyroid stimulating hormone (TSH). Diagnosis is typically established biochemically by low free thyroxine (fT4) and inappropriately low or normal TSH levels after excluding all other causes of discordant thyroid function test (TFT). Here, we report a case of a baby girl who presented with prolonged jaundice at day 15 of life with normal cord blood TSH performed as routine screening for congenital hypothyroidism. Serial TFT revealed declining serum fT4 with normal TSH consistent with CCH. Her jaundice resolved prior to levothyroxine replacement. CCH is commonly missed on cord blood TSH-based newborn screening leading to a delay in diagnosis, potentially resulting in neurodevelopmental delay. Hence, although CCH has a lower incidence than congenital primary hypothyroidism, a high index of suspicion is essential for timely diagnosis.